Large-area thickness measurement of transparent multi-layer films based on laser confocal reflection sensor - Choi, Young Man; Yoo, Hongki; Kang, Dongwoo (Measurement: Journal of the International Measurement Confederation, 2020)
It is critical to maintain uniform coating thicknesses over large area in order to manufacture high-quality coated transparent films. Optical thickness measurement technique gives relatively short measurement time and non-destructive measurement. Among the available optical techniques, a laser confocal method that detects reflected light at the interfaces between layers provides highly reliable and accurate height information. Because confocal sensors utilize focusing optics, both the numerical aperture of the focusing lens and refractive index of the film material must be considered when calibrating the actual thickness from the recorded displacement of the focusing lens. In this paper, we proposed a measurement method calibrated for the actual thickness of single- and double-layer transparent films. Also, we developed a large-area thickness measurement system for transparent substrates and the uniformity of hard-coated samples is evaluated using the laser confocal reflection sensor. Experimental results are compared with the thickness measured using a mechanical thickness gauge.
Keywords: Confocal; Measurement methods; Non-destructive measurement; Numerical aperture; Optical thickness measurements; Short measurement time; Transparent films; Transparent substrate; Confocal; Hard coating; Thickness measurement; Transparent film